Lilin Aroma terapi Bunga Telang (Clitoria Ternatea L.) untuk Pemberdayaan Kewirausahaan Sosial sebagai UMKM Masyarakat di Kelurahan Kapias Pulau Buaya Kecamatan Teluk Nibung Kota Tanjung Balai - Damayanti, Alfina; Mardiana, Juli; Limbong, Abdul Kalam; Adnir, Farid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Scented candles can be alternative treatments using vapor from essential oils of various kinds of plants that can be inhaled to calm various conditions. Generally aromatherapy is done for the purpose of increasing mood, altering cognitive areas, and also can be used as an additional drug. The study aims to make a ready scented candle of sunflowers (Clitoria ternatea L.) for empowerment of social entrepreneurship as part of Kapias Pulau Buaya Village community and into an effort to improve the economy of local entrepreneurs. Research methods used for socialization and monitoring methods performed in the hall of the Al-Islamiyah mosque in August 2023. Studies show that these telase-scented candles are in solid form, light blue, aromatherapy is typical, and a percentage of the public's enthusiasm for understanding materials during aromatherapy training by 95%, with a 100% percentage of whole societies getting motivated to practice in the manufacture of scent candles, and 70% of society is motivated to become entrepreneurs. Keywords: Aromatherapy Candles, Butterfly Pea (Clitoria ternatea), Empowerment of social entrepreneurship